The The Relationship between Early Breastfeeding Initiation (IMD) and Husband's Support with Exclusive Breastfeeding in the Paserpan Community Health Center - cindy nur permatasari; Novita Eka Kusuma W., SST., M.Keb.; Ahdatul Islamiah, S.Tr.Keb., M.Keb.; Dwi Purwanti, S.Kp., S.ST., M.Kes (Jurusan Kebidanan Politeknik Kesehatan Kemenkes Surabaya, 2024)
Babies get the best nutrition from breast milk (ASI). Breast milk is the best source of nutrition. WHO is targeting 50% of babies to be exclusively breastfed by 2021, but only 40% of babies are exclusively breastfed according to its data. Internal and external factors are the causes of the inability to exclusively breastfeed. The type of analytical observation used in this research is the cross-sectional method. This research involved breastfeeding mothers who worked in the Puskesmas work area. The purposive sampling method produced a total of 87 samples. used a questionnaire to assess husband's support for exclusive breastfeeding and Early Breastfeeding Initiation (IMD) assessment. Data analysis was carried out univarate and bivarate using the chi-square test. The results of the analysis show that 79.3% of respondents practice IMD, 51.7% are mostly supported by their husbands, and 71.3% practice exclusive breastfeeding. The results of the research show that IMD with Exclusive Breastfeeding has a p value of 0.001 which means it is related, while Husband Support with Exclusive Breastfeeding has a p value of 0.025 which means it is related. This study found that IMD and husband's support were related to providing exclusive breastfeeding to breastfeeding mothers at the Paserpan Community Health Center, Pasuruan Regency. It is hoped that the puskesmas can improve the exclusive breastfeeding management program and ask breastfeeding mothers to continue to provide exclusive breastfeeding because exclusive breastfeeding is the main component in providing the best nutritional intake for babies.